Post-Traditionalism in Indonesia: Tracking of Muhammad Abid al-Jabiri’s Thought - Abdul Mukti (Jurnal Ushuluddin, 2023)
The articulation of Muslims in Indonesia, as well as in other parts of the Islamic world, is a reflection of the dialectic between normative and historical Islamic teachings. In the historicity aspect, the articulation can be influenced by one of them, the dialectic of thought. This study aims to find traces and influences of the thoughts of Muhammad Abdi al-Jabiri, a contemporary Muslim thinker, on the dynamics of Islamic thought in Indonesia in the contemporary era. This study is library research that traces various works of al-Jabiri, which influenced Islamic thought in Indonesia with a hermeneutical approach, especially Gadamer's hermeneutics and Karl Manheim’s model of knowing sociology. From the results of tracking and studying these issues, it was found that al-Jabiri's thoughts influenced the younger generation of Muslims affiliated with the Nahdlatul Ulama tradition of thought. Some of the young generations of educated NU have used al-Jabiri's thoughts as a reference in developing the dynamics of thought by calling itself a school of Islamic post-traditionalism